2008
DOI: 10.1139/w08-091
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock-induced oxidative stress and antioxidant response in Aspergillus niger 26

Abstract: To extend the knowledge about the relationship between heat shock and oxidative stress in lower eukaryotes, the filamentous fungus Aspergillus niger 26 was chosen as a model system. Here, the response of A. niger cells to heat shock is reported. The temperature treatment significantly increased the levels of reactive oxygen species, superoxide anions (O2), and hydrogen peroxide and the rate of cyanide-resistant respiration as a marker of oxidative stress. Enhanced reactive oxygen species generation coincided w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 37 publications
2
29
0
12
Order By: Relevance
“…For A. kawachii, cultivation at 40°C appears to induce a stress response because several heat shock proteins and chaperones are significantly upregulated at this temperature, based on the results of GO analysis (Table 4). This finding is in agreement with a previous report that found that heat shock stress induces oxidative stress and an antioxidant response in A. niger, resulting in increased accumulation of the storage carbohydrates trehalose and glycogen (38). It was suggested that trehalose mobilization is required to facilitate cell recovery by A. niger after heatinduced damage (39).…”
Section: Discussionsupporting
confidence: 93%
“…For A. kawachii, cultivation at 40°C appears to induce a stress response because several heat shock proteins and chaperones are significantly upregulated at this temperature, based on the results of GO analysis (Table 4). This finding is in agreement with a previous report that found that heat shock stress induces oxidative stress and an antioxidant response in A. niger, resulting in increased accumulation of the storage carbohydrates trehalose and glycogen (38). It was suggested that trehalose mobilization is required to facilitate cell recovery by A. niger after heatinduced damage (39).…”
Section: Discussionsupporting
confidence: 93%
“…Apoptosis has been observed in a number of filamentous fungi, such as Aspergillus nidulans, Aspergillus fumigatus, Neurospora crassa, and Fusarium oxysporum (12)(13)(14)(15). Various physiological stresses, ionizing radiation, and hyperthermia have been reported to trigger apoptosis in fungi and cancer cells (14)(15)(16).…”
mentioning
confidence: 99%
“…Various physiological stresses, ionizing radiation, and hyperthermia have been reported to trigger apoptosis in fungi and cancer cells (14)(15)(16). However, the precise mechanism of hyperthermia-induced apoptosis in mammalian cells is not clear.…”
mentioning
confidence: 99%
“…Similar changes have been reported for other fungi and yeasts: Fusarium decemcellulare (35), P. chrysogenum (42), Saccharomyces cerevisiae (28), Candida albicans (32) etc. our previous studies also demonstrated enhanced RoS production in Humicola lutea and Aspergillus niger cells, threated by cu-and heat stress, respectively (1,30).…”
Section: At Cold Temperaturesmentioning
confidence: 65%
“…A variety of exogenous stimuli, such as radiation, pathogen infections, and exposure to xenobiotics can also cause in vivo RoS production (29). Additionally, several specific types of environmental stress can lead to the production of RoS, including heat stress (1), herbicide/insecticide contamination (2,3), ultraviolet light exposure (4,21), etc.…”
Section: Introductionmentioning
confidence: 99%